Celebrity worship dengan compulsive buying pada k-popers di Surabaya - Prameswari, Firsty Hernie Karlina; Riskasari, Windah; Patrika, Fauziah Julike (Fakultas Psikologi Universitas Hang Tuah, 2024)
Abstract. Collecting merchandise in the form of photos of idols repeatedly, and buying goods frequently is an act of compulsive buying behavior. This research aimed to determine the relationship between celebrity worship and compulsive buying among K-Popers in Surabaya. Research respondents totaling 91 members of the Kloss Jjang community in Surabaya, aged 18 - 25 years, were selected using purposive sampling. The measuring instruments used were the Edwards Compulsive buying Behavior Scale (ECBS) and the Celebrity Attitude Scale (CAS). Data were analyzed using product moment correlation techniques. The research results showed that celebrity worship and compulsive buying had a positive connection. The results of this research are expected to lead to interventional discussions regarding celebrity worship for prevention and or compulsive buying.